2018
DOI: 10.1556/1326.2017.00317
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro propagation affects the composition of narrow-leaved lavender essential oils

Abstract: The aim of this study was to identify and determine by means of gas chromatography–flame ionization detector (GC–FID) and gas chromatography–mass spectrometry (GC–MS) method the volatile compounds of essential oils obtained from three varieties of narrow-leaved lavender grown in the field and in in vitro cultures. The essential oils were isolated by hydrodistillation in Deryng apparatus. It was found that the analyzed essential oils varied in terms of chemical composition depending on the variety and condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Micropropagation of lavender plants also caused a decrease in the diameter of secretory trichomes, compared with field-grown plants. According to the research conducted by Andrys and Kulpa (2017), the composition of essential oils isolated from tissue of in vitro propagated lavender differs from that of oils isolated from field-grown plants, which could have an effect on the increased antioxidant and antimicrobial activities of micropropagated plants in comparison with field-grown lavender. Increased antioxidant and antimicrobial activities of essential oils and extracts make them suitable for direct industrial use, especially by the cosmetics industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Micropropagation of lavender plants also caused a decrease in the diameter of secretory trichomes, compared with field-grown plants. According to the research conducted by Andrys and Kulpa (2017), the composition of essential oils isolated from tissue of in vitro propagated lavender differs from that of oils isolated from field-grown plants, which could have an effect on the increased antioxidant and antimicrobial activities of micropropagated plants in comparison with field-grown lavender. Increased antioxidant and antimicrobial activities of essential oils and extracts make them suitable for direct industrial use, especially by the cosmetics industry.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro plant propagation stresses the plant, and the presence of macro-and microelements in the medium and their transport within the plant do not only influence its growth, but also cause an increase in the concentration of biologically active substances which play the role of antioxidants (Khenifi et al 2011). Andrys and Kulpa (2017) demonstrated that in vitro propagation of plants results in a changed chemical composition of essential oils and promotes the synthesis of antioxidant compounds such as carvacrol and thymol, which may affect the antioxidant activity of extracts from in vitro and field-grown plants (Baser et al 1991). Higher values of the antioxidant potential of extracts obtained from in vitro plants may also stem from the fact that the damaging of plant tissue for the purpose of conducting tissue cultures and its introduction into the medium results in an increase in the level of jasmonic acid (JA) in the plant, resulting in the expression of protective genes, thus causing an accumulation of secondary metabolites (Creelman andMullet 1997, Kant et al 2004).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Linalool, lavandulol, and their esters (linalyl acetate and lavandulyl acetate) are responsible for the fresh and floral smell of lavender oil. Moreover, the quality of oil depends on both a high content of linalool and linalyl acetate and their mutual proportions (preferably higher than 1) [34].…”
Section: Resultsmentioning
confidence: 99%
“…The explants used for the experiment were single-node shoot fragments and apical shoot fragments with several leaves and the apical meristem. They were placed on the Murashige and Skoog (MS) media [ 125 ] with the addition of 2 mg dm −3 of kinetin and 0.2 mg dm −3 of indole-3-acetic acid [ 126 ] and 1, 2, 5, 10, 20, or 50 mg dm −3 of AgNPs or AuNPs. The medium pH was set at 5.7 using 0.1 M solutions of HCl and NaOH.…”
Section: Materials and Study Methodsmentioning
confidence: 99%